Legal Position and Collaboration Pattern of Village Government and Village Community Institutions in the Management of Village-Owned Enterprises (Bumdes): (Study of Teja Perceka Bumdes, Rajagaluh District) - Muhammad Lanang Gilang Gumilang; Harmono Harmono (Ann Publisher, 2026)
Background. This paper departs from a simple anxiety: why BUMDes, which are normatively designed as a shared space between the village government and the community, often fail to operate in a completely balanced way in practice. This study seeks to examine the problem through the case of BUMDes Teja Perceka in Rajagaluh District, by tracing how the legal positions of the actors are practiced, how the pattern of relationships is formed, and where the legal problems lie. Method. The approach used is empirical law with a socio-legal perspective, so that what is seen is not only the rules but also how they are implemented in daily life. Results. From the field, it can be seen that the division of authority that has been normatively formulated is not completely limited in practice. The village government is still in a decisive position in the direction of BUMDes policies, while on the other hand, the role of village community institutions has not developed as a truly influential participatory force. The relationships that are formed are closer to coordination that is not entirely equal than deliberative collaboration. In such a situation, the main problem lies not in the lack of rules, but in how they work or do not work in institutional practice. Conclusion. This research has found that strengthening BUMDes is not enough to be pursued through a normative approach alone. What is more urgent is how authority is translated into operational terms, how supervision is carried out in practice, and how the space for participation is opened up, not merely as a formality. Without it, BUMDes will continue to be in a position between two options: recognized as an independent business entity, yet operating in a relationship that still depends on the power of the village government.